해양위성 데이터의 메타데이터 표준화 및 활용 사례 연구 - 정성훈; Seong-hoon Jeong (한국항행학회논문지, 2024)
해양위성 데이터는 복잡한 시공간적 특성을 가지며, 이를 체계적으로 관리하고 상호운용성을 확보하기 위해 표준화된 메타데이터의 개발이 요구된다. 본 연구는 국제 표준(ISO 19115, ISO/IEC 11179)과 국내 표준을 통합하여 JSON, XML, RDF, CSV 형식으로 메타데이터를 설계하고 생성하는 프레임워크를 제안하였다. 연구 과정은 메타데이터 요소 정의, 스키마 설계, 생성, 검증을 포함하며, 데이터 품질 관리와 상호 운용성을 보장하기 위해 JSONLint, XML Editor Online, EasyRDF, Online CSV Editor와 같은 도구를 활용하였다. 또한, 표준 통합 로직과 형식 변환 엔진을 설계하였으며, 실증 사례를 통해 메타데이터 작성 및 검증 방법을 구체적으로 제시하고, 데이터 활용성 증대와 시스템 간 데이터 교환의 원활성을 확인하였다. 이 연구의 결과는 메타데이터 표준화가 데이터의 일관성, 신뢰성, 접근성을 향상시키고 데이터 기반 의사결정의 효율성을 높이고자 하였다. 향후 연구에서는 새로운 데이터 형식의 반영과 추가적인 표준화 작업을 통해 메타데이터 관리의 확장성과 일관성을 더욱 강화할 필요가 있다. Marine satellite data exhibits complex spatiotemporal characteristics, necessitating the development of standardized metadata for systematic management and interoperability. This study proposes a framework for designing and generating metadata in JSON, XML, RDF, and CSV formats by integrating international standards (ISO 19115, ISO/IEC 11179) and domestic standards. The research process includes defining metadata elements, schema design, generation, and validation, utilizing tools such as JSONLint, XML Editor Online, EasyRDF, and Online CSV Editor to ensure data quality and interoperability. Additionally, a standard integration logic and a format conversion engine were developed. Through case studies, the study provides a detailed methodology for metadata creation and validation, confirming improved data usability and seamless data exchange between systems. The results demonstrate that metadata standardization enhances data consistency, reliability, accessibility, and improves the efficiency of data-driven decision-making. Future research should focus on incorporating new data formats and advancing additional standardization efforts to further strengthen the scalability and consistency of metadata management.